Targeting the autophagy-lysosomal pathway in Huntington disease: a pharmacological perspective - Yang, Junsheng; Zhang, Chaoyue (Frontiers in Aging Neuroscience, 2023)
The autophagy-lysosomal pathway (ALP) is the major biological pathway responsible for clearing intracellular protein aggregates, therefore a promising target for treating diseases featuring the accumulation of aggregation-prone proteins, such as Huntington disease (HD). However, accumulating evidence indicated that targeting ALP to treat HD is pharmacologically challenging due to the complexity of autophagy and the autophagy defects in HD cells. Here in this mini-review, we summarized the current challenges in targeting ALP in HD and discussed a number of latest findings on aggrephagy and targeted protein degradation, which we believe will provide potential new targets and new strategies for treating HD via ALP.